Method for evaluating microstructure of hydration product of composite solid waste-based alkali-activated cementing material
By combining SEM-EDS, nano-indentation, FTIR and MIP and other technical means, multi-angle evaluation was carried out, and the problem of imperfect research on the microstructure of hydration products of solid waste base-excited gelling materials was solved, and the evaluation quality and speed were improved. Provides more accurate support for the research and development and application of materials.
Patent Information
- Application Number
- CN202411507336.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The prior art is difficult to comprehensively and thoroughly evaluate the microstructure of hydration products of solid waste base-activated gelling materials, which affects its performance optimization and the expansion of its application scope.
A variety of technical means are used, including SEM-EDS, nanoindentation, FTIR, MIP, etc., to conduct multi-angle and comprehensive evaluation, and through cross-control analysis, a comprehensive understanding of the microstructure of the hydrated products is understood.
It improves the evaluation quality and speed, provides more accurate data support, and helps promote the research and development and application of composite solid waste base excitation materials.
Smart Images

Figure CN119395065A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of green and environmentally friendly road materials, and relates to a method for evaluating the microstructure of hydration products of alkali-activated cementitious materials, and in particular to a method for evaluating the microstructure of hydration products of composite solid waste-based alkali-activated cementitious materials. Background Art
[0002] With the increasing global attention to sustainable development and environmental protection, the production and use of traditional building materials such as silicate cement face problems such as large resource consumption, high carbon emissions and difficult waste treatment. Therefore, the development of new environmentally friendly and high-performance building materials has become a research hotspot. Alkali-activated materials, as an emerging green building material, have gradually attracted widespread attention from academia and industry due to their advantages such as low preparation cost, high strength and good durability. Alkali-activated materials are mainly composed of two parts: aluminosilicate minerals and alkali activators. Aluminosilicate minerals usually come from industrial waste residues, such as slag, fly ash, metakaolin, silica fume, steel slag, etc. These waste residues are not only widely available, but also can effectively realize the resource utilization of solid waste. Alkali activators mainly include caustic soda (such as NaOH), alkali-containing silicates, aluminates, etc., which promote the hydration reaction of aluminosilicate minerals through catalysis.
[0003] The reaction mechanism of alkali-activated materials mainly involves the dissolution of SiO2 and Al2O3 on the surface of aluminosilicate minerals by alkali activators. Under the action of alkali activators, the Si-O-Si bonds and Al-O-Al bonds on the surface of raw materials are broken to form intermediate products such as orthosilicic acid and aluminosilicate. These products further diffuse in the liquid phase and undergo polycondensation to form geopolymer gels with a spatial network structure. As the reaction time increases, the geopolymer gel may further form zeolite-like microcrystals or semi-crystalline structures, thereby giving the material high strength and durability. The hydration products of alkali-activated materials mainly include hydrated aluminosilicate gels (CASH) and aluminosilicate gels. These gels are composed of multiple [SiO4] and [AlO4] tetrahedrons connected by bridging oxygen to form a complex spatial network structure. Among them, CSH gel, cross-linked gel (CNASH), calcium-rich alkali-activated gel (CASH) and sodium-rich alkali-activated gel (NASH) are the main hydration products of alkali-activated solid waste materials, and their structure and properties directly affect the overall performance of the material. In addition, depending on the characteristics of the solid waste material and the type of activator, other types of hydration products may also be formed, such as hydrotalcite, AFt phase minerals, etc.
[0004] At present, the main technical means used to evaluate the microstructure of the hydration products of cementitious materials include scanning electron microscope-energy dispersive X-ray spectrometer (SEM-EDS), transmission electron microscope (TEM), X-ray diffraction (XRD), infrared spectroscopy (FTIR), low-field nuclear magnetic resonance (LNMR), nanoindentation, thermogravimetric analysis (TGA), mercury intrusion method (MIP), etc. However, these methods have the following advantages and disadvantages: Scanning electron microscope (SEM) is mainly used for high-resolution micro-area morphology analysis, which can provide magnified morphology images and is suitable for analyzing the surface microstructure of the hydration products of solid waste cementitious materials. Its advantages are intuitiveness and high resolution, but its disadvantage is that it cannot observe the internal microstructure of the material. Transmission electron microscope (TEM) can observe the internal microstructure of the sample, including the morphology and distribution of the hydration products. It has deeper penetration than SEM and can reveal fine structures less than 0.2 microns, namely submicrostructure and ultrastructure. Its advantage is that it can provide more comprehensive structural information, but its disadvantage is that the sample preparation process is relatively complicated, which can easily lead to errors in experimental data, and is generally not recommended. X-ray diffraction (XRD) is mainly used to analyze the crystal structure of materials and can determine the chemical composition and crystal structure of hydration products. Its advantages are high analysis accuracy and the ability to provide quantitative chemical composition information, but its disadvantage is that the analysis effect on amorphous materials is poor. Infrared spectroscopy (FTIR) is used to analyze the chemical bonds and functional groups of materials and can infer the chemical structure of hydration products. Its advantages are that it is sensitive to changes in the chemical environment and can provide rich chemical structure information, but its disadvantage is that it cannot directly provide morphology and structural information. Low-field nuclear magnetic resonance (LNMR) can clearly observe the structure and dynamic changes of hydrogen atoms and improve high-resolution images, but its disadvantage is that compared with high-field nuclear magnetic resonance, the signal-to-noise ratio and resolution may be slightly lower, and some specific studies require nuclear magnetic equipment with higher field strength, which may affect the accuracy of observation and analysis. Nanoindentation is considered to be an effective technology for measuring the nano / micro mechanical properties of cementitious materials. It is used to measure the nano-level hardness and elastic modulus of cementitious materials and reveal the mechanical properties of materials at the microscopic scale, but this technology requires professional equipment and operating techniques. Thermogravimetric analysis (TGA) is used to evaluate the thermal stability of cementitious materials and study their mass changes at different temperatures, thereby analyzing the thermal decomposition characteristics and components of the materials. However, for some complex materials, the analysis results of this method may not be accurate enough. Mercury intrusion porosimetry (MIP) is used to determine the pore structure and pore size distribution of cementitious materials and understand the density and permeability of the materials. This is of great significance for optimizing the preparation process and performance of cementitious materials, such as controlling the pore structure of cementitious materials to improve their strength and durability. However, this technology is destructive to samples and the operation process is relatively complicated.
[0005] Solid waste cementitious materials are widely used in building materials, especially in pavement base materials, showing great potential, but there is still a problem of incomplete microstructure research. Solid waste cementitious materials, as a new type of cementitious material using industrial solid waste as raw materials, are gradually becoming the focus of the building materials industry. It not only realizes the recycling of resources, but also shows excellent performance and greater application potential. In the fields of civil engineering, road engineering, etc., the base and concrete prepared with solid waste cementitious materials can meet the requirements of various strength grades, and significantly improve the corrosion resistance and crack resistance of medium and low strength grade concrete. However, as a pavement base material, the microstructure of solid waste cementitious materials is not thoroughly studied, which affects the further optimization of its performance and the expansion of its application range. Therefore, strengthening the research on the microstructure of solid waste cementitious materials is of great significance to promote its application in pavement base materials. Summary of the invention
[0006] In order to solve the above technical problems existing in the background technology, the present invention provides a microstructure evaluation method of hydration products of composite solid waste-based alkali-activated cementitious materials, which can improve the evaluation quality and evaluation speed.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A method for evaluating the microstructure of a hydration product of a composite solid waste-based alkali-activated cementitious material, characterized in that the method comprises the following steps:
[0009] 1) Preparing composite solid waste-based alkali-induced gelling specimens;
[0010] 2) curing the composite solid waste-based alkali-induced gelling specimen prepared in step 1);
[0011] 3) performing SEM-EDS detection, nanoindentation detection, FTIR detection and MIP detection on the composite solid waste alkali-induced gelling specimen after step 2), and obtaining detection results, which include SEM-EDS detection results, nanoindentation detection results, FTIR detection results and MIP detection results;
[0012] 4) Select any two of the test results obtained in step 3) for cross-reference analysis, and finally conduct a multi-angle and comprehensive evaluation of the microstructure of the hydration product of the composite solid waste-based alkali-activated cementitious material.
[0013] Preferably, the step 1) the composite solid waste based alkali-activated gelling specimen comprises a precursor and an alkali activator; the alkali-activated material in the composite solid waste based alkali-activated gelling specimen is carbide slag; when preparing the composite solid waste based alkali-activated gelling specimen, sodium silicate or sodium hydroxide solid is used to replace 5%, 10%, 15% and 20% of the mass of the carbide slag; the modulus and dosage of the alkali activator are selected based on the principle that the compressive strength is maximized after the alkali activator is mixed with the precursor and cured for 28 days; the precursor is red mud, fly ash and / or circulating fluidized bed fly ash; the water-cement ratio of the composite solid waste based alkali-activated gelling is calculated based on the optimal moisture content measured by the static pressure molding method.
[0014] Preferably, the curing time in step 2) is 28 days, the curing temperature is 20°C±1°C, and the curing relative humidity is 95%.
[0015] Preferably, the specific implementation method of performing SEM-EDS detection in step 3) is:
[0016] a.1) The composite solid waste-based alkali-induced gelling specimen after step 2) is subjected to a loading rate of 0.6 MPa / s, and the non-lateral compressive strength of the composite solid waste-based alkali-induced gelling specimen is measured using a MATEST 3000kN compression testing machine to obtain the non-lateral compressive strength results and the partial composite solid waste-based alkali-induced gelling specimen after the non-lateral compressive strength is destroyed;
[0017] a.2) immersing part of the composite solid waste-based alkali-induced gelling specimen obtained in step a.1) in anhydrous ethanol to stop the hydration reaction inside the composite solid waste-based alkali-induced gelling specimen;
[0018] a.3) placing the composite solid waste alkali-activated gelling specimen obtained in step a.2) in a vacuum oven at 60°C and drying for 24 hours;
[0019] a.4) polishing the surface of the composite solid waste-based alkali-activated gelling specimen obtained in step a.3) to obtain a smooth surface;
[0020] a.5) conducting a conductive treatment on the composite solid waste alkali-activated gelling specimen obtained in step a.4), performing SEM-EDS detection, and obtaining a BSE image;
[0021] a.6) Analyze the BSE image obtained in step a.5) using ImageJ software to obtain SEM-EDS detection results.
[0022] Preferably, the specific implementation method of performing nanoindentation detection in step 3) is:
[0023] b.1) Determine the non-lateral compressive strength of the composite solid waste-based alkali-induced gelling specimen after step 2) using a MATEST 3000kN compression testing machine at a loading rate of 0.6MPa / s, and obtain the non-lateral compressive strength results and the partial composite solid waste-based alkali-induced gelling specimen after non-lateral compressive strength destruction;
[0024] b.2) immersing part of the composite solid waste-based alkali-induced gelling specimen obtained in step b.1) in anhydrous ethanol to stop the hydration reaction inside the composite solid waste-based alkali-induced gelling specimen;
[0025] b.3) placing the composite solid waste alkali-activated gelling specimen obtained in step b.2) in a vacuum oven at 60°C and drying for 24 hours;
[0026] b.4) polishing the composite solid waste-based alkali-activated gelling specimen obtained in step b.3) to obtain a smooth surface;
[0027] b.5) preparing an indentation grid, wherein the indentation grid is an M×N matrix structure, and the gap between the indentation grid is no more than 5 μm;
[0028] b.6) Using a ladder mode loading program and an unloading program, the indentation grid obtained in step b.5) is pressed onto the smooth surface obtained in step b.4) for nanoindentation testing, and finally the nanoindentation test result is obtained.
[0029] Preferably, in step b.6), the loading rate is no more than 400 μN / s, the maximum loading amount is no more than 2000 μN / s, and after reaching the maximum loading amount, the loading time is 2 s; the unloading process does not exceed 5 s.
[0030] Preferably, the specific implementation method of performing FTIR detection in step 3) is:
[0031] c.1) taking part of the powder of the composite solid waste alkali-activated gelling specimen after step 2) as a specimen sample;
[0032] c.2) preparing MS residue, HCl residue and water residue respectively based on the test piece samples obtained in step c.1);
[0033] c.3) OMNIC software was used to obtain spectra of HCl and MS selectively dissolved hydration products.
[0034] Preferably, the preparation method of the MS residue in step c.2) is: dissolving the test piece sample obtained in step c.1) in an MS solution, stirring the mixture with a magnetic stirrer, vacuum filtering the suspension, washing the insoluble residue with methanol, drying and weighing to obtain the MS residue; the MS solution is a solution formed by dissolving 6.25 g of salicylic acid in 100 ml of methanol;
[0035] The preparation method of the HCl residue in step c.2) is: adding the test piece sample obtained in step c.1) into a 1.76wt% HCl solution for extraction to obtain an insoluble residue, which is the HCl residue;
[0036] The water residue in step c.2) is prepared by dissolving the paste of the test piece sample obtained in step c.1) in distilled water, dissolving in an ultrasonic bath at 25° C. for 5 hours, centrifuging at 10,000 rpm for not less than 10 minutes, and retaining the residue, which is the water residue;
[0037] The specific implementation method of c.3) is: using OMNIC software to subtract the HCl residue spectrum and the MS residue spectrum from the original gelled sample powder spectrum to obtain the spectrum of HCl and MS selective dissolution hydration products.
[0038] Preferably, the specific implementation method of the step of performing FTIR detection further comprises, after step c.3):
[0039] c.4) further analyzing and confirming the spectra of the HCl and MS selectively dissolved hydration products obtained in step c.3) by TGA method to obtain FTIR detection results; in the TGA method, the heating rate of the hydration product is 10°C / min, and the heating temperature is increased from 20°C to 1200°C.
[0040] Preferably, the specific implementation method of performing MIP detection in step 3) is:
[0041] d.1) taking the composite solid waste-based alkali-induced gelling specimen after no lateral compressive strength damage in step a.1);
[0042] d.2) crushing the composite solid waste alkali-activated gelling specimen obtained in step d.1) into specimen particles of 5nm-10nm;
[0043] d.3) drying the sample particles obtained in step d.2) at -90°C under vacuum conditions in a freeze dryer for 36 hours;
[0044] d.4) taking out the dried product in step d.3) and placing it in an oven at 25° C. to obtain a MIP test sample;
[0045] d.5) Performing a MIP test on the MIP test sample obtained in step d.4) to obtain a MIP test result.
[0046] Compared with the prior art, the present invention has the following advantages and effective results:
[0047] The present invention provides a method for evaluating the microstructure of hydration products of composite solid waste based alkali-activated cementitious materials, comprising the following steps: 1) preparing a composite solid waste based alkali-activated cementitious material specimen; 2) curing the composite solid waste based alkali-activated cementitious material specimen prepared in step 1); 3) performing SEM-EDS detection, nanoindentation detection, FTIR detection and MIP detection on the composite solid waste based alkali-activated cementitious material specimen after step 2), and obtaining detection results at the same time, wherein the detection results include SEM-EDS detection results, nanoindentation detection results, FTIR detection results and MIP detection results; 4) selecting any two detection results obtained in step 3) for cross-reference analysis, and finally performing multi-angle and comprehensive evaluation on the microstructure of hydration products of composite solid waste based alkali-activated cementitious materials. The present invention aims to solve the defect of the existing technical means of single microstructure analysis of complex hydration products of composite solid waste base alkali activated materials, and adopts a variety of technical means, including scanning electron microscope-energy dispersive X-ray spectrometer (SEM-EDS), ImageJ software image analysis, nanoindentation test, infrared spectrometer (FTIR) and OMNIC software spectrum subtraction analysis, thermogravimetric analysis (TGA) and MIP mercury intrusion instrument, etc., to evaluate the hydration products of composite solid waste base alkali activated cementitious materials from multiple angles and in an all-round manner. By comprehensively using a variety of technical means, the present invention can more comprehensively understand the microstructure of the hydration product, and realize the multi-angle and all-round evaluation of the microstructure of the hydration product of the composite solid waste base alkali activated cementitious material, thereby improving the quality and speed of the evaluation, and providing more accurate data support for the research and development and application of composite solid waste base alkali activated materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 The composite solid waste-based alkali-induced gelling test piece prepared by the present invention;
[0049] Figure 2 This is the SEM scanning electron microscope image of red mud;
[0050] Figure 3 This is the SEM image of circulating fluidized bed fly ash;
[0051] Figure 4 This is the SEM image of carbide slag;
[0052] Figure 5 This is the SEM image of fly ash;
[0053] Figure 6This is the phase image after processing by ImageJ. DETAILED DESCRIPTION
[0054] The present invention provides a method for evaluating the microstructure of hydration products of composite solid waste-based alkali-activated cementitious materials, which is a comprehensive and systematic evaluation method, and specifically comprises the following steps:
[0055] 1) Preparation of composite solid waste-based alkali-induced gelling test specimens. At least 4 specimens of each type are prepared. The prepared composite solid waste-based alkali-induced gelling test specimens are as follows: Figure 1 As shown;
[0056] The alkali-activated material is carbide slag (CS), and then sodium silicate (Na2SiO3) or sodium hydroxide (NaOH) solid is used to replace 5%, 10%, 15% and 20% of the mass of carbide slag (CS) to prepare the alkali-activated gelling agent. The modulus and dosage of the alkali-activated gelling agent are selected based on the principle that the compressive strength of the alkali-activated gelling agent after mixing with the precursor (red mud (RM), fly ash (FA), circulating fluidized bed fly ash (CFBFA) etc.) and curing for 28 days is the largest. The composite solid waste-based alkali-activated gelling agent specimen is prepared by mixing the precursor (which can be one or more) to be studied and analyzed, the composite alkali-activated material and water until uniform. The water-binder ratio of the composite solid waste-based alkali-activated gelling agent is calculated based on the best water content measured by the static pressure molding method.
[0057] 2) Curing of the specimens: the curing time is 28 days; the specimens need to be wrapped with plastic film and cured for 28 days under standard curing conditions of 20℃±1℃ and relative humidity of 95%.
[0058] 3) After the specimens were subjected to non-lateral compressive strength tests, the hydration products of the cementitious materials were analyzed using scanning electron microscopy-energy dispersive X-ray spectrometry (SEM-EDS);
[0059] For the specimens after curing, the non-lateral compressive strength of each specimen shall be measured using a MATEST 3000kN compression testing machine at a loading rate of 0.6MPa / s;
[0060] The sample used for the SEM-EDS test in step (3) is 1-2g of the central part of the specimen without lateral compressive strength failure, which is then immersed in anhydrous ethanol for 7 days to stop the hydration reaction inside. The sample is then placed in a vacuum oven at 60°C and dried for 24 hours;
[0061] To ensure the preservation performance of the sample, the sample must be wrapped with epoxy resin under vacuum conditions before the SEM-EDS experiment; when performing the SEM-EDS test, the sample must be removed from the epoxy resin and polished until a smooth surface is obtained. Finally, the sample is immersed in anhydrous ethanol and placed in an ultrasonic bath to remove various particles attached to the sample surface. After polishing, the sample is dried in a vacuum oven at 60°C for 12 hours, and the sample is subjected to conductive treatment for SEM-EDS analysis. The specific test method is as follows:
[0062] Analysis conditions: high vacuum environment, accelerating voltage 25keV, working distance 15.0mm;
[0063] Imaging method: Backscattered electron (BSE) imaging is used to improve the signal-to-noise ratio and image contrast, and to distinguish the gelled area from other areas such as unreacted precursors;
[0064] Point analysis strategy: Through EDS point analysis, collect no less than 80 points from the sample focusing only on the gelation area, remembering to exclude the precursors that do not participate in the reaction, to study the composition of the gelation;
[0065] Research objective: To study and analyze the distribution composition of different elements in the gelling area.
[0066] 4) Image analysis of BSE images obtained from SEM-EDS analysis was performed using ImageJ software;
[0067] The application requirements of ImageJ software in BSE image analysis in step (4) are:
[0068] Image preprocessing: Use ImageJ software to open the BSE image obtained by SEM-EDS analysis, and use the color threshold function of the software to preprocess the image.
[0069] Phase separation and color assignment: By setting a specific color threshold, the different reaction phases and unreacted phases of the gel can be effectively separated, and each phase can be assigned a different color for easy distinction and identification.
[0070] Image combination and percentage calculation: The segmented images were combined into a composite map of gel paste, and the percentage of each phase was calculated and determined using the Define Scale function of ImageJ software.
[0071] Multi-site analysis: To ensure the accuracy and reliability of the analysis, more than 5 different sites were selected for each sample for image analysis, and the average value was taken as the final result.
[0072] 5) Perform nanoindentation test on the gelled sample material;
[0073] The samples used for nanoindentation testing were prepared in a similar manner to those for SEM-EDS in step (3), but the polishing of the samples required a detailed grinding process lasting up to 25 minutes to obtain an extremely smooth surface;
[0074] In order to achieve accurate indentation testing, a square grid layout consisting of 144 points is carefully selected, which is in the form of 12 rows × 12 columns to ensure the comprehensiveness and accuracy of the test. The grid gap is precisely set to 5μm, and this precise setting ensures high resolution of the test data.
[0075] In the selection of loading and unloading procedures, the trapezoidal mode is adopted, which is widely recognized in material testing for its stability and reliability. The loading rate is strictly controlled to 400μN / s to ensure the smooth progress of the test process and avoid unnecessary impact or damage to the sample. The maximum load is set to 2000μN / s, which not only ensures the adequacy of the test, but also avoids deformation or damage to the sample due to overload. After reaching the maximum load, this state is maintained for 2s to ensure the stability and reliability of the test results. Subsequently, the unloading process is smoothly completed within 5s. This operation not only ensures the continuity of the test, but also avoids additional stress or damage to the sample due to unloading too quickly.
[0076] 6) The composition and reaction degree of the hydrated gelation products of the precursor and the alkaline activator were studied by selective dissolution process with infrared spectroscopy (FTIR) and OMNIC software for spectral subtraction analysis;
[0077] The samples used for Fourier transform infrared (FTIR) analysis in step (6) include: 1-2 g powder in the center of the gelled specimen, water residue, HCl residue and MS residue. The preparation of the three residues is as follows:
[0078] 1. Preparation of MS residues:
[0079] The gelled sample powder and the raw materials were dissolved in MS solution (specific ratio: 100 ml methanol and 6.25 g salicylic acid); the mixture was stirred using a magnetic stirrer, and the suspension was vacuum filtered; the insoluble residue was washed with methanol, weighed after drying, and stored in a vacuum desiccator.
[0080] 2. Preparation of HCl residue:
[0081] 2 g of gelled sample paste was added to 300 ml of HCl solution (HCl solution was prepared by mixing 37 wt % concentrated hydrochloric acid and purified water in a volume ratio of 1:20) for extraction; during the extraction, unreacted CFBFA and silica gel were left as insoluble residues.
[0082] 3. Preparation of water residue:
[0083] 2 g of the gelled sample paste was dissolved in 300 g of distilled water in an ultrasonic bath at 25° C. for 5 hours; after dissolution, the solution was centrifuged to separate the residue from the liquid to obtain a water residue.
[0084] The dissolution of hydration products from gelled samples was investigated using OMNIC software. The spectra of HCl and MS residues were subtracted from the original gelled sample powder spectra to obtain spectra of hydration products selectively dissolved by HCl and MS.
[0085] 7) The hydration products of the powder samples were further analyzed and confirmed by thermogravimetric analysis (TGA);
[0086] In step (7), when further analyzing and confirming the hydration products of the gelled sample powders by thermogravimetric analysis (TGA), it is ensured that each powder sample is about 5-10 mg, and the heating rate of all samples is 10°C / min, and the temperature is increased from 20°C to 1200°C.
[0087] 8) Use MIP mercury intrusion porosimeter to study the pore structure of powder samples;
[0088] Step (8) The void structure of the gelled powder sample is studied by using a MIP mercury intrusion instrument. The powder sample is crushed into a particle size of 5nm-10nm by a crushing instrument such as a ball mill. Then, it is dried in a freeze dryer at a temperature of -90°C and a small vacuum pressure for 36 hours. After drying, it is taken out and placed in an oven at 25°C until the MIP test is performed.
[0089] 9) In combination with steps 3) to 8), a multi-angle and comprehensive evaluation is conducted on the microstructure of the hydration product of the composite solid waste-based alkali-activated cementitious material.
[0090] Any two microscopic analyses in steps (3)-(8) can be compared with each other. By cross-analyzing the microstructure of the hydration products of composite cementitious materials using six technical means, the hydration products of composite solid waste-based alkali-activated cementitious materials can be evaluated from multiple angles and in an all-round manner.
[0091] The technical solution provided by the present invention is described in detail below in conjunction with the accompanying drawings:
[0092] Embodiment 1:
[0093] A method for evaluating the microstructure of a composite solid waste-based alkali-activated cementitious material hydration product comprises the following steps:
[0094] (1) Preparation of composite solid waste alkali-induced gelling specimens
[0095] In this example, the solid waste-based precursors used are red mud (RM) and circulating fluidized bed fly ash (CFBFA), and the alkaline activator uses carbide slag (CS). The above three materials are subjected to X-ray fluorescence analysis (XRF). The results are shown in Table 1. The main components of the precursors are SiO2, Al2O3, CaO, Fe2O3, etc., among which the total content of SiO2 and Al2O3 exceeds 50%, and can be used as a geopolymer precursor. The CaO content in the alkaline activator carbide slag (CS) is as high as 83.39%, which reacts with water to generate Ca(OH)2, creating an alkaline environment, thereby increasing the reaction rate of red mud (RM) and circulating fluidized bed fly ash (CFBFA).
[0096] Table 1 Chemical composition test table of raw materials
[0097]
[0098] Red mud (RM) comes from the Bayer red mud produced by an aluminum plant in Shanxi Province. It was used in this experiment after being piled up for about a year. Because the piled red mud is blocky particles, it needs to be crushed into powder using a jaw crusher. Because the red mud is relatively wet at this time, it must be placed in a dry blower for drying, and then a screening machine is used to pass the dried powdered red mud through a 0.30mm square hole sieve for testing. The SEM electron microscope image of the red mud is as follows: Figure 2 As shown, it can be seen from the microscopic picture that the red mud particles are agglomerated. On the surface, it can be seen that the structure is loose and porous, and the pores between the particles are relatively dense. These pores are disordered and irregular, and most of the pores are between particles. The contact area between soil particles is relatively small. There are many shapes as a whole, such as block, strip, elliptical and other particle forms. Under a high-power scanning electron microscope, the surface of the red mud agglomerate may be honeycomb-like, and the walls of the large and small holes are closely connected; the circulating fluidized bed fly ash (CFBFA) comes from a thermal power plant in Shanxi Province, and its SEM electron microscope image is shown below Figure 3 As shown in the figure, the appearance of CFB ash under the scanning electron microscope is mainly irregular, loosely structured slag-like particles, and its particle size is usually large. The specific surface area is relatively large, which is conducive to the formation of hydration products; calcium carbide slag (CS) comes from a steel plant in Shanxi Province, and its SEM electron microscope image is shown in the figure below. Figure 4 As shown in the figure, it can be observed that carbide slag particles have various forms, such as flakes, blocks and a few strips, and there are obvious pore structures between the particles. These pore structures contribute to the material transport and adsorption performance of carbide slag in chemical reactions.
[0099] The mixing ratios of RM, CFBFA and CS were 40%, 50% and 10% respectively. After adding 20g of carbide slag to 80g of red mud and 100g of circulating fluidized bed fly ash, the mixture was fully stirred in a small mixer at a speed of 800r / min. Then, 36g, 38g, 40g, 42g, 44g and 46g of distilled water were added respectively. Six groups of 50mm×50mm×50mm cylindrical specimens with water contents of 18%, 19%, 20%, 21%, 22% and 23% were prepared by static pressure molding test (such as Figure 1 After forming, the mass and height of the sample were weighed and measured respectively. After calculating the dry density, the moisture content-dry density quadratic curve was fitted using drawing software such as Excel. The optimal moisture content was 20.5% using the capture tool. Then, 41 g of water was added each time according to the optimal moisture content obtained above, and 4 parallel test pieces were prepared according to the above steps.
[0100] (2) Maintenance of specimens
[0101] The four parallel test pieces prepared in step (1) are wrapped and sealed with at least three layers of plastic film, and then placed in a curing box for curing for 28 days under standard curing conditions of 20°C ± 1°C and a relative humidity of 95%.
[0102] (3) No lateral compressive strength and SEM-EDS test
[0103] After the specimens after curing were subjected to a non-lateral compression test at a loading rate of 0.6 MPa / s, four values were obtained, namely: 14.793 MPa, 15.322 MPa, 15.611 MPa, and 14.677 MPa. The average value of 15.101 MPa was taken as the final result of the test.
[0104] After the non-lateral compressive strength test, take 2g of gelled samples from the center of each crushed specimen, immerse them in anhydrous ethanol for 7 days to prevent the solid waste base from inducing gelling hydration reaction, and then put them in a vacuum oven at 60°C for 24 hours; before SEM-EDS, wrap the dried samples with epoxy resin, and polish the samples to obtain a smooth surface 14 hours before the test, and remove various particles on the surface of the samples in an ultrasonic bath filled with anhydrous ethanol, and then put them in an oven at 60°C for 12 hours. After drying, spray gold on the samples for conductive treatment, and then formally conduct SEM-DES test. The specific test process is as follows:
[0105] In a high vacuum environment, an acceleration voltage of 25keV and a working distance of 15.0mm, backscattered electron (BSE) imaging is used to improve the signal-to-noise ratio and image contrast. After the magnification ratio is determined to obtain a clear image, the gelled area and unreacted precursor areas are distinguished (the precursor needs to be subjected to SEM in advance to determine its microscopic appearance structure in order to distinguish the various phase areas in this step); then, the gelled area obtained by the distinction is concentrated to collect no less than 80 points to study the elements in the micro-area of the gelled material for detailed analysis, and further determine the distribution composition of different elements in the gelled area.
[0106] (4) Quantitative gel composition using ImageJ
[0107] The BSE image obtained in step (3) is preprocessed using the color threshold function of the ImageJ software; various reaction phases and unreacted phases of the gel are effectively separated by setting a specific color threshold, and each phase is assigned a specific color for easy distinction; the segmented images are then combined with the gel for composite mapping. The specific steps of this step are as follows:
[0108] 1) Image segmentation: Splitting the original image into multiple parts, perhaps for more detailed processing or analysis of specific areas of the image.
[0109] 2) Gel image processing: Perform necessary processing on the gel image, such as brightness adjustment, noise reduction, etc., to obtain a clear gel image.
[0110] 3) Image combination and pasting: The segmented image parts are combined as needed and pasted with the processed gel image.
[0111] 4) Composite Mapping: Finally, these images are composite mapped to generate a complete image containing all necessary information, such as Figure 6 shown.
[0112] Using the grayscale and scale functions of ImageJ software, four different points were selected for each sample for image analysis, the percentage of each phase was calculated, and the average value of each phase was taken as the final result.
[0113] Table 2 Phase percentage test table
[0114]
[0115] (5) Nanoindentation test
[0116] The samples used for nanoindentation testing were prepared in a similar way to those used in SEM-EDS tests, except that the polishing of the samples during this treatment required 25 minutes of fine grinding until an extremely smooth surface was obtained;
[0117] In order to achieve the purpose of accurate indentation testing, a representative square grid layout consisting of 144 points was selected, which was in the form of 12 rows × 12 columns to ensure the comprehensiveness and accuracy of the test. The gap of the grid was precisely set to 5μm, and this precise setting ensured the high resolution of the test data; in addition, the trapezoidal mode was adopted in the selection of loading and unloading procedures, which is widely recognized in material testing for its stability and reliability. The loading rate was strictly controlled to 400μN / s to ensure the smooth progress of the test process while avoiding unnecessary impact or damage to the sample. The maximum load was set to 2000μN / s, which not only ensured the adequacy of the test, but also avoided deformation or damage to the sample due to overload. After reaching the maximum load, this state was maintained for 2s to ensure the stability and reliability of the test results. Subsequently, the unloading process was completed smoothly within 5s, which not only ensured the continuity of the test, but also avoided additional stress or damage to the sample due to unloading too quickly.
[0118] (6) Infrared spectroscopy (FTIR) combined with OMNIC software to further analyze the hydration products
[0119] The present invention adopts a selective dissolution process, and combines an infrared spectrometer (FTIR) and OMNIC software to perform spectral subtraction analysis, aiming to deeply explore the composition and reaction degree of the precursor and the hydration gel product of the alkali activator. The samples used in the Fourier transform infrared spectroscopy (FTIR) experiment include 2g of powder in the center of the specimen after the lateral compressive strength test in step (3) and three residues. The specific experimental process is as follows:
[0120] 1) Preparation of MS residue: The gelled sample powder and the raw material were dissolved in a specific ratio of MS solution (100 ml methanol + 6.25 g salicylic acid), stirred with a magnetic stirrer and the suspension was vacuum filtered. The insoluble residue was washed with methanol, dried, weighed and stored.
[0121] 2) Preparation of HCl residue: The gelled sample paste was added to an HCl solution (the HCl solution was prepared by mixing 37 wt % concentrated hydrochloric acid and purified water in a volume ratio of 1:20) for extraction, and the unreacted CFBFA and silica gel were left as insoluble residues.
[0122] 3) Preparation of water residue and spectral analysis: The gelled sample powder was dissolved in distilled water, and the residue and liquid were separated by centrifugation after ultrasonic dissolution. The spectrum of the selectively dissolved hydration product was analyzed by subtracting the HCl and MS residue spectra from the original gelled sample powder spectrum using OMNIC software.
[0123] (7) Thermogravimetric analysis (TGA)
[0124] Before the experiment, it is necessary to judge the elemental composition in SEM-EDS in advance whether there are chemical substances that will react with the crucible of thermogravimetric analysis, thereby causing damage to the crucible and contamination of the reactants. Therefore, before the experiment, a crucible of non-reactive material should be selected according to the sample for testing. In this case, due to the presence of Si-containing oxides, ordinary alumina crucibles cannot be used, and platinum crucibles must be used. First, 5-10 mg of sieved powdered samples are evenly spread on the bottom of the crucible (note that the particle size of the same series of samples must be controlled within a similar range to ensure the reliability of the test data as much as possible);
[0125] During the test, the relationship between the mass of the substance and the temperature is measured under program-controlled temperature (heating rate is 10℃ / min, temperature increases from 20℃ to 1200℃). The thermogravimetric curve (TG curve) is recorded, with the ordinate being the weight percentage and the abscissa being the temperature or time;
[0126] Finally, data analysis is performed to analyze the change of sample weight with temperature / time through TG curve. The first-order derivative can be selected to obtain DTG curve to analyze the weight change rate. The area of DTG curve is proportional to the weight loss and can be used for further analysis.
[0127] (8) MIP mercury intrusion test
[0128] In order to study and analyze the void microstructure of the hydration products of composite solid waste-based alkali-activated cementitious materials, it was decided to use the MIP mercury injection test. The powder sample preparation process used in this test is as follows: First, the gel blocks that have undergone no lateral compressive strength test are crushed using a ball mill or other crushing instrument until the particle size reaches 5nm-10nm. Subsequently, the crushed samples are dried using a freeze dryer at a temperature of -90°C and a small vacuum pressure for 36 hours. After drying, about 3g of the sample is taken out and placed in an oven at 25°C until the MIP (mercury injection porosimetry) test is performed; during the test, the instrument is calibrated first, and then the engineer sets the appropriate pressure range and step size according to the sample type and expected pore range; when the sample is loaded into the sample chamber, it should be ensured that the sample is well sealed with the instrument, and then mercury injection is performed to start the test. Finally, the analysis of the test data should be carried out in the following two steps:
[0129] 1) Exclude abnormal data: During data analysis, identify and exclude abnormal data points, such as sudden pressure drops or sudden volume changes. 2) Curve fitting: Use a suitable model to fit the pressure-volume curve to accurately calculate the pore size distribution.
[0130] (9) Comprehensive analysis
[0131] Any two microscopic analysis techniques in steps (3)-(8) can be cross-analyzed. By cross-analyzing and comparing the six different microstructure techniques used in the hydration products of composite cementitious materials, the characteristics of the hydration products of composite solid waste-based alkali-activated cementitious materials can be deeply evaluated and analyzed from multiple angles and in all directions, thereby ensuring the comprehensiveness and accuracy of the analysis. This example performs the following cross-analysis and comparison:
[0132] The SEM-EDS analysis results were compared with the nanoindentation test results to analyze the relationship between microstructure and mechanical properties. The FTIR spectrum analysis results were compared with the thermogravimetric analysis results to verify the composition and reaction degree of the hydration products; the MIP mercury porosimeter analysis results were correlated with the results of other technical means to fully understand the impact of pore structure on the performance of cementitious materials. Through the cross-analysis and comparison of the above steps, the characteristics of the hydration products of composite solid waste-based alkali-activated cementitious materials can be deeply evaluated and analyzed from multiple angles and in an all-round manner.
[0133] Example 2
[0134] A method for evaluating the microstructure of a composite solid waste-based alkali-activated cementitious material hydration product comprises the following steps:
[0135] (1) Preparation of composite solid waste alkali-induced gelling specimens
[0136] In this example, the solid waste-based precursors used are red mud (RM) and fly ash (FA), and the alkaline activators used are carbide slag (CS) and sodium silicate (Na2SiO3) solids. X-ray fluorescence analysis (XRF) was performed on the above three materials, and the results are shown in Table 2.
[0137] Table 2 Chemical composition test table of raw materials
[0138]
[0139] Red mud (RM) and carbide slag (CS) are the same as those in Example 1. Fly ash (FA) comes from a power plant in Shanxi Province. Figure 5 As shown in the figure, the appearance of fly ash (FA) under electron microscope scanning is irregular, with spherical particles accounting for the majority. The surface of these spherical particles is quite smooth, and under magnified observation, it can be seen that many tiny glass balls are adhered to the surface of these particles. In addition, fly ash also contains loose sponge-like glass particles, the surface of these particles is basically smooth, and there are also honeycomb-like appearance features with spherical insides.
[0140] The proportions of RM, FA and CS were 45%, 45% and 10% respectively. After adding 20g of carbide slag to 90g of red mud and 90g of fly ash, the mixture was fully stirred by a small mixer at a speed of 800r / min, and then 32g, 34g, 36g, 38g, 40g and 42g of distilled water were added respectively. Six groups of 50mm×50mm×50mm cylindrical specimens with moisture contents of 16%, 17%, 18%, 19%, 20% and 21% were prepared by static pressure molding test. After molding, the mass and height were measured respectively. After calculating the dry density, the moisture content-dry density quadratic curve was fitted using drawing software such as excel, and the optimal moisture content was obtained by the capture tool as 18.5%. Then, 37g of water was added each time according to the optimal moisture content obtained above, and 4 parallel specimens were prepared according to the above steps. Then, sodium silicate (Na2SiO3) solid was used to replace 5%, 10%, 15% and 20% of the mass of carbide slag (CS) to prepare four parallel test pieces according to the above method. The rest of the test steps refer to Example 1.
Claims
1. A method for evaluating the microstructure of hydration products of composite solid waste-based alkali-activated cementitious materials, characterized in that: The method for evaluating the microstructure of the hydration product of composite solid waste-based alkali-activated cementitious material comprises the following steps: 1) Preparation of composite solid waste-based alkali-induced gelling specimens; 2) curing the composite solid waste-based alkali-induced gelling specimen prepared in step 1); 3) performing SEM-EDS testing, nanoindentation testing, FTIR testing and MIP testing on the composite solid waste-based alkali-induced gelling specimen after step 2), and obtaining test results, which include SEM-EDS test results, nanoindentation test results, FTIR test results and MIP test results; 4) Select any two of the test results obtained in step 3) for cross-reference analysis, and finally conduct a multi-angle and comprehensive evaluation of the microstructure of the hydration product of the composite solid waste-based alkali-activated cementitious material.
2. The method for evaluating the microstructure of hydration products of composite solid waste-based alkali-activated cementitious materials according to claim 1, characterized in that: The step 1) comprises a composite solid waste based alkali-activated gelling specimen including a precursor and an alkali activator; the alkali-activated material in the composite solid waste based alkali-activated gelling specimen is carbide slag; sodium silicate or sodium hydroxide solid is used to replace 5%, 10%, 15% and 20% of the carbide slag mass when preparing the composite solid waste based alkali-activated gelling specimen; the modulus and dosage of the alkali activator are selected based on the principle that the compressive strength is maximized after the alkali activator is mixed with the precursor and cured for 28 days; the precursor is red mud, fly ash and / or circulating fluidized bed fly ash; the water-cement ratio of the composite solid waste based alkali-activated gelling is calculated based on the optimal moisture content measured by the static pressure molding method.
3. The method for evaluating the microstructure of hydration products of composite solid waste-based alkali-activated cementitious materials according to claim 2, characterized in that: The curing time in step 2) is 28 days, the curing temperature is 20°C±1°C, and the curing relative humidity is 95%.
4. The method for evaluating the microstructure of hydration products of composite solid waste-based alkali-activated cementitious materials according to claim 1, 2 or 3, characterized in that: The specific implementation method of performing SEM-EDS detection in step 3) is: a.1) The composite solid waste-based alkali-induced gelling specimen after step 2) is subjected to a loading rate of 0.6 MPa / s, and the non-lateral compressive strength of the composite solid waste-based alkali-induced gelling specimen is measured using a MATEST 3000kN compression testing machine to obtain the non-lateral compressive strength results and the partial composite solid waste-based alkali-induced gelling specimen after non-lateral compressive strength destruction; a.2) immersing part of the composite solid waste-based alkali-induced gelling specimen obtained in step a.1) in anhydrous ethanol to stop the hydration reaction inside the composite solid waste-based alkali-induced gelling specimen; a.3) placing the composite solid waste-based alkali-activated gelling specimen obtained in step a.2) in a vacuum oven at 60°C and drying for 24 hours; a.4) polishing the surface of the composite solid waste-based alkali-activated gelling specimen obtained in step a.3) to obtain a smooth surface; a.5) Conducting a conductive treatment on the composite solid waste alkali-activated gelling specimen obtained in step a.4), performing SEM-EDS testing, and obtaining a BSE image; a.6) Use ImageJ software to analyze the BSE image obtained in step a.5) to obtain the SEM-EDS detection results.
5. The method for evaluating the microstructure of hydration products of composite solid waste-based alkali-activated cementitious materials according to claim 1, 2 or 3, characterized in that: The specific implementation method of the nanoindentation test in step 3) is: b.1) The composite solid waste-based alkali-induced gelling specimen after step 2) is subjected to a loading rate of 0.6 MPa / s, and the non-lateral compressive strength of the composite solid waste-based alkali-induced gelling specimen is measured using a MATEST 3000kN compression testing machine to obtain the non-lateral compressive strength results and the partial composite solid waste-based alkali-induced gelling specimen after non-lateral compressive strength destruction; b.2) immersing part of the composite solid waste-based alkali-induced gelling specimen obtained in step b.1) in anhydrous ethanol to stop the hydration reaction inside the composite solid waste-based alkali-induced gelling specimen; b.3) placing the composite solid waste-based alkali-activated gelling specimen obtained in step b.2) in a vacuum oven at 60°C and drying for 24 hours; b.4) polishing and grinding the composite solid waste-based alkali-activated gelling specimen obtained in step b.3) to obtain a smooth surface; b.5) preparing an indentation grid, wherein the indentation grid is an M×N matrix structure, and the gap between the indentation grid is no more than 5 μm; b.6) Using the ladder mode loading and unloading procedures, the indentation grid obtained in step b.5) is pressed onto the smooth surface obtained in step b.4) for nanoindentation testing, and finally the nanoindentation test results are obtained.
6. The method for evaluating the microstructure of hydration products of composite solid waste-based alkali-activated cementitious materials according to claim 5, characterized in that: In the step b.6), the loading rate is no more than 400 μN / s, the maximum loading amount does not exceed 2000 μN / s, and after reaching the maximum loading amount, the loading time is 2 s; the unloading process does not exceed 5 s.
7. The method for evaluating the microstructure of hydration products of composite solid waste-based alkali-activated cementitious materials according to claim 1, 2 or 3, characterized in that: The specific implementation method of performing FTIR detection in step 3) is: c.1) taking part of the powder of the composite solid waste alkali-activated gelling specimen after step 2) as a specimen sample; c.2) preparing MS residue, HCl residue and water residue respectively based on the test piece samples obtained in step c.1); c.3) OMNIC software was used to obtain spectra of HCl and MS selective solubilization hydration products.
8. The method for evaluating the microstructure of hydration products of composite solid waste-based alkali-activated cementitious materials according to claim 7, characterized in that: The preparation method of the MS residue in step c.2) is: dissolving the test piece sample obtained in step c.1) in the MS solution, stirring the mixture with a magnetic stirrer, vacuum filtering the suspension, washing the insoluble residue with methanol, drying and weighing to obtain the MS residue; the MS solution is a solution formed by dissolving salicylic acid in methanol at a solid-liquid ratio of 6.25 g:100 ml; The preparation method of the HCl residue in step c.2) is: adding the test piece sample obtained in step c.1) into a 1.76wt% HCl solution for extraction, and obtaining an insoluble residue, which is the HCl residue; The water residue in step c.2) is prepared by dissolving the paste of the test piece sample obtained in step c.1) in distilled water, dissolving in an ultrasonic bath at 25°C for 5 hours, centrifuging at 10,000 rpm for not less than 10 minutes, and retaining the residue, which is the water residue; The specific implementation method of c.3) is: using OMNIC software to subtract the HCl residual spectrum and the MS residual spectrum from the original gelled sample powder spectrum to obtain the spectrum of HCl and MS selectively dissolved hydration products.
9. The method for evaluating the microstructure of hydration products of composite solid waste-based alkali-activated gelling materials according to claim 8, characterized in that: The specific implementation method of the step of performing FTIR detection further includes, after step c.3), c.4) The spectra of the HCl and MS selectively dissolved hydration products obtained in step c.3) are further analyzed and confirmed by TGA method to obtain FTIR detection results; in the TGA method, the heating rate of the hydration product is 10°C / min, and the heating temperature is increased from 20°C to 1200°C.
10. The method for evaluating the microstructure of hydration products of composite solid waste-based alkali-activated cementitious materials according to claim 4, characterized in that: The specific implementation method of performing MIP detection in step 3) is: d.1) taking the composite solid waste-based alkali-induced gelling specimen after no lateral compressive strength damage in step a.1); d.2) crushing the composite solid waste alkali-activated gelling specimen obtained in step d.1) into specimen particles of 5nm-10nm; d.3) drying the sample particles obtained in step d.2) in a freeze dryer at -90°C under vacuum conditions for 36 hours; d.4) taking out the dried product in step d.3) and placing it in an oven at 25°C to obtain a MIP test sample; d.5) Performing a MIP test on the MIP test sample obtained in step d.4) to obtain a MIP test result.
Citation Information
Patent Citations
Low-cost solid waste-based cementing material
CN113045226A
Method for evaluating shale surface mineral mechanical property based on nanoindentation test
CN115791476A
Circulating fluidized bed fly ash-based cementing material, preparation method and formula design method
CN118561559A